2015
DOI: 10.2139/ssrn.2701821
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Activities and Systemic Risk

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…3.4.1) . Furthermore, we differentiate business activities according to their degree of innovation, thus classifying them as either traditional or nontraditional insurance business, as is common in the literature (see, e.g., Baluch et al., ; Kessler, ; Cummins and Weiss, and Berdin and Sottocornola, , instead use the terms core and noncore activities). This classification is not always clear‐cut but, in general, we consider an activity to be traditional when its accompanying risks are mostly (1) idiosyncratic, (2) not correlated with one another, and (3) not influenced by economic business cycles (see IAIS, ) .…”
Section: Systemic Risk In the Insurance Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…3.4.1) . Furthermore, we differentiate business activities according to their degree of innovation, thus classifying them as either traditional or nontraditional insurance business, as is common in the literature (see, e.g., Baluch et al., ; Kessler, ; Cummins and Weiss, and Berdin and Sottocornola, , instead use the terms core and noncore activities). This classification is not always clear‐cut but, in general, we consider an activity to be traditional when its accompanying risks are mostly (1) idiosyncratic, (2) not correlated with one another, and (3) not influenced by economic business cycles (see IAIS, ) .…”
Section: Systemic Risk In the Insurance Sectormentioning
confidence: 99%
“…Their results support the view that banks contribute the most to systemic risk. See also Berdin and Sottocornola ().…”
mentioning
confidence: 99%
“…Their findings reveal that size is the main driver of insurers' exposure and contribution to systemic risk in the U.S., and the exposure to systemic risk additionally depends on non-traditional and non-insurance activities like CDS writing. Berdin and sottocornola (2015) apply linear Granger causality test, ΔCoVaR, MES to measure systemic for bank, insurance, and non-financial sectors in Europe. They find that the insurance industry shows a persistent systemic relevance over time and plays a subordinate role in causing systemic risk compared to banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 2007-2009 financial crisis has revealed that the insurance sector was partly responsible of the crisis with American International Group (AIG) becoming the first example of an insurer in the U.S. that received federal assistance to prevent bankruptcy due to it being considered as systemically important. As a consequence, regulators such as Solvency II board, Financial Stability Board (FSB), the International Association of Insurance Supervisors (IAIS) have raised concern about identifying, monitoring, and mitigating systemic risk in the insurance Berdin and sottocornola (2015) apply linear Granger causality test, conditional value at risk (CoVaR,) and MES to analyse systemic risk in the Eurozone banking, insurance, and non-financial sector.…”
Section: Introductionmentioning
confidence: 99%
“…total exposures and activities. However, as Berdin and Sottocornola (2015) showed, certain activities, which do not only include insurance activities such as life or non-life lines of business, but also certain balance sheet items or certain managerial practices such as leverage or funding structures, tend to drive the contribution to systemic risk of insurers beyond the size of the institution or beyond the aggregated systemic contribution of the single institution. 4 To be more precise, in our analysis we considered the cross-section (i.e.…”
Section: The Evolution Of the Existing Macroprudential Frameworkmentioning
confidence: 99%